Long-term mechanical properties of cellulose fibre-reinforced cement mortar with diatomite - Ince, Ceren; Derogar, Shahram; Ball, Richard James; Ekinci, Abdullah; Yuzer, Nabi (EMERALD GROUP PUBLISHING LTD, 2019)
This paper presents a study investigating the long-term mechanical properties of cellulose fibre-reinforced cement mortars incorporating diatomite as a replacement material for quartz sand. Important properties including mass, compressive and flexural strength, sorptivity, water penetration depth and porosity have been rigorously investigated. Significant findings demonstrated that increasing the replacement level of diatomite resulted in a systematic decrease in the final mass of cellulose fibre-reinforced cement mortars and a dramatic increase in both flexural and compressive strength. In the short term, sorptivity, water penetration depth and porosity were enhanced, whereas the pozzolanicity of diatomite provided long-term strength gain over the 6 month period of study. Microstructural development of mortars, confirmed using scanning electron microscopy, revealed a denser, more compact structure in the diatomite specimens, which was consistent with the physical property measurements. This research supports the development of environmentally friendly diatomite-based mortars for construction.
Keywords: compressive strength; permeability; pozzolans; PARTIAL REPLACEMENT; SILICA FUME; COMPOSITES; MICROSTRUCTURE; STRENGTH; Construction & Building Technology; Materials Science